CORPORATE SOCIAL RESPONSIBILITIES (CSR) OF SELECTED ORGANIZATIONS IN PONDICHERRY REGION - AN EXPLORATORY RESEARCH. - Porkodi, T.; Porkodi, T.; Venkatramaraju, D. (International Journal of Psychosocial Rehabilitation, 2020)
Corporate Social Responsibility (CSR) is a thought whereby Industrial organizations consider the interests of people by taking responsibility for the impact of their activities on customers, employees, shareholders, communities and the environment in all aspects of their business operations. It is also concentrated on how companies manage their business processes to produce an overall positive impact on society. It concentrates sustainability, social impact, and moral principles, and done appropriately should be about main business activities and how companies make their money through their business, not just add-on extras such as activities executed philanthropically. A 2015 research study conducted by the Kenexa High-Performance Institute in London city had known that Industrial organizations that had an unadulterated commitment to CSR significantly outperformed those that did not, with an average return on wealth 19 times higher. Additionally, the study showed that CSR orientated companies had a higher level of employee commitment and offered a noticeably better standard of customer service. In this context, the present study analyses the performance of corporate social responsibilities and its impact on the society in selected Industrial Organization in the Pondicherry region.